Babesia gibsoni internal transcribed spacer 1 region is highly conserved amongst isolates from dogs across Japan - LIU, Mingming; CAO, Shinuo; VUDRIKO, Patrick; SUZUKI, Hiroshi; SOMA, Takehisa; XUAN, Xuenan (Journal of Veterinary Medical Science, 2016)
Babesia gibsoni is a tick-borne apicomplexan parasite of dogs that often causes fever and hemolytic anemia with highly variable clinical outcome. In this study, we sequenced the 254bp Internal Transcribed Spacer 1 region (ITS1) of 54 B. gibsoni isolates from 14 different geographical regions of Japan. The 54 isolates shared high sequence identity with each other and with B. gibsoni isolates reported in GenBank database (97.2–100%). Consistent with previous reports, phylogenetic analysis showed that B. gibsoni isolates from Japan formed the same clade with those from U.S.A., Australia, India and Taiwan. Our finding indicates that B. gibsoni ITS1 region is highly conserved among isolates from dogs in Japan, making it a useful genetic marker for molecular epidemiology of the parasite.